The Effect Of Synergetic Teaching Method oj Students' Logical and Mathematical Thinking Abilities on Social Arithmetics Material In Grade VII - Yosi Maria Marito Napitupulu; Lolyta Damora Simbolon; Simon Panjaitan (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This study aims to determine the effect of the Synergistic Teaching method on students' logical mathematical thinking ability in the Social Arithmetic material of grade VII at SMP Negeri 1 Berampu in the 2025/2026 academic year, and to measure the magnitude of the influence. The research method used is quantitative with a simple linear regression approach. Based on the results of the analysis, the average value of students' logical mathematical thinking ability is 80.5, with the lowest value being 50 and the highest value being 100, which is included in the "good" category. Observations on the application of the Synergistic Teaching method show an average value of 83.667, also categorized as good. The resulting regression equation is Ŷ = 19.929 + 0.724X, which indicates a positive relationship between the two variables. The results of the F test show that F count > F table (15.357 > 4.2), so H₀ is rejected and Hₐ is accepted, meaning that there is a significant influence of the Synergistic Teaching method on students' logical mathematical thinking ability. The correlation coefficient r = 0.634 shows a fairly strong relationship, and the t-test also shows tcount > ttable (4.338 > 1.701). Therefore, it can be concluded that the Synergistic Teaching method has a significant influence on students' logical mathematical thinking abilities in the Social Arithmetic material.